Using non-destructive testing to predict bending modulus of carbon infiltrated-carbon nanotubes. (23rd September 2019) - Fagergren, Fred; Sypherd, Shane; Snow, Dan; Cunningham, Andrew; Jensen, Brian
Abstract: Carbon infiltrated carbon nanotubes (CI-CNT) are an important emerging material in several micro-electro-mechanical systems (MEMS) because of their unique mechanical and chemical properties. While CI-CNTs are only roughly conductive they work well in micro springs, levers, and meshes. However, fabrication of CI-CNTs can result in large mechanical property variation, and methods to characterize properties usually involve destructive testing. Destructive testing also assumes the tested specimens are representative of the entire batch which is not always true in the case of CI-CNT production. Finding a non-destructive way to test for stiffness of this material reduces the number of parts that have to be made and increases confidence in the integrity of device being used. It also simplifies testing of complex parts. The stiffness of CI-CNT beams is related to the molecular structure of the carbon material infiltrated between the carbon nanotubes (CNTs), how it interacts with the CNTs, and how much of it there is. The amount of material can be approximated with the density of the beam, and both the type of material and its interaction with the CNTs can be approximated through analysis of the Raman spectra taken at the surface. A combination of these two observations can be related to the effective material stiffness. The relationship can be fitted with a power function, with a variance of 1.41 GPa, which is about 11% of the maximum stiffness of the samples tested.